SEGREGASI PASCA KONFLIK, COMMUNAL DISCOURSE DAN MATERIAL CULTURE BAGI PENGUATAN AGAMA DAN KEBANGSAAN DI MALUKU - Nelson Semol Kalay (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2020)
There are many impacts of the conflict Ambon that occurred years ago which are still found in society. Two of them are collective trauma memory and settlement religious-based segregation. The focus of this article is the communal discourse on the settlement pattern of religious-based segregation. The theory as the basic perspective of this study is a socio-linguistic theory developed by Norman Fairclough through Critical Discourse Analysis Approach. The principle notion of this approach is that discourse has an important role in shaping a society. Therefore, the aim of this article is to remind all that because of the complexity faced by the society after the conflict, trust-building, and trauma-healing are programs that all must work on, especially when one talks about religion and nationalism in the Moluccas context.